2015
DOI: 10.2139/ssrn.2659596
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Ambiguity Preferences

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…7,[17][18][19][20][21][22] Value-based decision processes have received a lot of attention in the field of NE, which provides a set of methods to assess individual preference characteristics. 23 It has already been shown that understanding these individual preferences can be used to enhance existing models of motor control (MDM). 8,18,19 MDM can be represented using a fundamental NE principle of utility maximization, where utility is a concept used to describe behavior in value-based choice tasks (for dictionary see Table 1).…”
Section: Neuroeconomics Approaches To Motor Control Assessmentmentioning
confidence: 99%
“…7,[17][18][19][20][21][22] Value-based decision processes have received a lot of attention in the field of NE, which provides a set of methods to assess individual preference characteristics. 23 It has already been shown that understanding these individual preferences can be used to enhance existing models of motor control (MDM). 8,18,19 MDM can be represented using a fundamental NE principle of utility maximization, where utility is a concept used to describe behavior in value-based choice tasks (for dictionary see Table 1).…”
Section: Neuroeconomics Approaches To Motor Control Assessmentmentioning
confidence: 99%
“…Therefore, in the current study, uncertainty referred to ambiguous scenarios. Based on Ellsberg's paradigm, Cavatorta and Schröder (2014) have developed the Dynamic Ellsberg Urn Task, where participants complete several rounds of selections between the risky and the ambiguous urns, but the distribution statistics in the risky urn changes each round according to participants' preceding response. For example, if a participant chooses the 50:50 risky option to begin with, the number of balls with reward will then decrease in the risky option; if the participant chooses the ambiguous option, the number will then increase.…”
Section: Induction (Esi)mentioning
confidence: 99%
“…For the purpose of this study, the Dynamic Ellsberg Social Task (DEST) was developed to measure participants' uncertainty attitude. It is a social variation of the original Dynamic Ellsberg Urn Task (Cavatorta & Schröder, 2014; Appendix F). The original task measures preference for external uncertainty determined purely by chance, but for the context of this study, this task was adapted to reflect real-lifeoriented social situations in which participants must make decisions under uncertainty.…”
Section: Dynamic Ellsberg Social Task (Dest)mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, risk aversion is rated on 10-point scales from "not at all willing to take risks" (1) to "very willing to take risks" (10). Based on instruments of Cavatorta and Schröder (2016), ambiguity tolerance is measured by using four statements indicating the extent to which you agree or disagree with them on a scale from 1 (strongly agree) to 7 (strongly disagree): (1) choice when the outcome is uncertain. Other variables we measure and report in the additional analyses include participants' qualification, their position, age, and gender.…”
Section: Additional Analysesmentioning
confidence: 99%